Unraveling the synergistic impact of entrepreneurial orientation, leadership competence, and digital marketing strategy on business performance of martabak smes in emerging markets - Nurul Hijriah; Abdul Arifin Ilham; Pratiwi Eka Widiyanti; Tri Devita Ariani (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2025)
This study examines the effects of Entrepreneurial Orientation (EO), Leadership Competence (LC), and Strategy Absorptive Capacity (SAC) on Digital Marketing Strategy (DMS) and Business Performance (BP) among MSMEs in West Java, Indonesia. Using a quantitative approach, data were collected from 465 food and beverage MSMEs and analyzed with Structural Equation Modeling (SEM). The results show that EO has a significant positive effect on SAC, while LC significantly influences DMS but does not affect SAC. SAC has a positive and significant effect on both DMS and BP, whereas DMS does not directly affect BP. The findings indicate that business performance is primarily driven by internal strategic capabilities, particularly strategy absorptive capacity, rather than digital marketing alone. This study highlights the importance of entrepreneurial orientation and strategic absorptive capacity in improving MSME performance in the digital era.